Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam ( PAI ) di kelas V dengan menggunakan Metode Umpan Balik - Donya Putra; Ahmad Joni (Kampus Akademik Publiser, 2024)
Islamic Religious Education (PAI) is one of the subjects that plays an important role in shaping students' character and religious understanding. However, the learning outcomes of fifth-grade students at SD Negeri 15 Ampang Gadang on the subject of Belief in the Last Day are still low, with a pre-cycle average score of only 5.18. This study aims to improve student learning outcomes through the application of the feedback method. The type of research used was Classroom Action Research (CAR) with 22 students as subjects. The research instruments included activity observation sheets, lesson plan assessments, learning implementation assessments, and learning outcome tests. The data were analyzed descriptively, quantitatively, and qualitatively through observation and reflection. The results showed a significant increase in the average student score, from 5.18 in the pre-cycle to 6.45 in cycle I, and further increased to 7.99 in cycle II. Thus, the use of the feedback method proved to be effective in improving student learning outcomes in Islamic Religious Education.